English Speaking Training for Hotel Staffs: A Study on Perception - Harahap, Muhammad Fadhly Pratama; Arini, Restu (Peneliti.net, 2024)
English in the hotel industry is considered crucial in order to provide service excellence in the term of communication with foreign tourists. Prioritizing the proficiency of staff in English indicates the importance of language choice in hotels to contribute to guest satisfaction, upgrade a positive brand image, and help build customer loyalty. To improve their English proficiency, an English speaking training program must be carried out. This study aims to investigate the perception of hotel staff towards English speaking training given to them. This study employed a descriptive quantitative method; data collected through questionnaires distributed to six staff of a hotel in Yogyakarta, Indonesia. The result reveals positive perceptions to the English speaking training for all aspects. Participants gained positive perception. The scores reached 3.78 for both speaking improvement and teaching method, while 3.79 for English speaking training materials. It concluded that the English speaking training enhanced participants' confidence and application of English speaking skills in their daily work.